Isolated Bilateral Ptosis as an Early Sign of Guillain-Barré Syndrome - Yahia Z. Imam; Dirk Deleu (Case Reports in Neurological Medicine)
Background. Guillain-Barré syndrome (GBS) has many variants with distinct presentations. Ptosis as an initial presentation is rare. Case Report. We describe a young female with bilateral ptosis without ophthalmoplegia as the initial presentation of Guillain-Barré ptosis in an anti-GQ1b IgG antibody negative patient with a favorable outcome to intravenous immunoglobulins. Objectives. Our paper highlights the importance of recognizing GBS as a potential etiology in a patient presenting with isolated ptosis, particularly since the course of GBS can be more dramatic than in the anti-GBQ1b syndromes such as ophthalmoparesis without ataxia and Miller Fisher syndrome or ocular myasthenia. Conclusion. This is the first paper of anti-GBQ1b antibody negative GBS presenting with isolated ptosis without ophthalmoparesis. GBS should be included in the list of differential diagnosis of such presentations.